Kinetics Study of the Formation of Pyrmidine Thione from the Reaction of 2,6-dibenzylidinecyclohexanone and its Derivatives with Thiourea - Kaka, Kosrat N.; Dabbagh, Abdul Majeed M.; Hamad, Wali M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2016)
Kinetics of the addition of thiourea to 2,6-dibenzylidenecyclohexanone and its derivatives have been studied. The reaction is found as a pseudo-first order process which includes a nucleophilic attack by thiourea at the carbonyl group of the ketone system to produce the heterocyclic pyrimidine thione "thiopyrimidine" (Claisen route mechanism). The effect of the substituents at the para position of the 2,6-dibenzylidenecyclohexanone and its derivatives on the rate of reaction, at different temperatures, is studied. Arrhenius parameters, entropies, enthalpies and free energies of activations are estimated. A suitable mechanism, which is correspondent with the results and with Claisen routes mechanism, is suggested for this reaction.